2023
DOI: 10.1186/s12866-023-02945-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and potential clinical applications of the extracellular vesicles of human pathogenic Fungi

Amir Ullah,
Yiyi Huang,
Kening Zhao
et al.

Abstract: Extracellular vesicles (EVs) are a heterogeneous group of lipid membrane-enclosed compartments that contain different biomolecules and are released by almost all living cells, including fungal genera. Fungal EVs contain multiple bioactive components that perform various biological functions, such as stimulation of the host immune system, transport of virulence factors, induction of biofilm formation, and mediation of host–pathogen interactions. In this review, we summarize the current knowledge on EVs of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…The lack of clear biomarkers has hampered deep investigations in EVs isolation and characterization and their biomedical applications. Fungal EVs may have unique biogenesis and cargo loading, and different fungal species may also be different, which needs to be further explored . Through FETEM and FESEM observations, together with particle size and potential analysis, it is suggested that M.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of clear biomarkers has hampered deep investigations in EVs isolation and characterization and their biomedical applications. Fungal EVs may have unique biogenesis and cargo loading, and different fungal species may also be different, which needs to be further explored . Through FETEM and FESEM observations, together with particle size and potential analysis, it is suggested that M.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles produced by C. albicans are richly equipped with various proteins and virulence factors, including numerous enzymes. Their activity may contribute to processes related to the physiology of fungi as well as the pathogenesis of infections they cause [20,42,43]. Molecules transported in vesicles may be more resistant to unfavorable environmental conditions and degradation [44] and act at a greater distance from pathogen cells settled in a particular host niche [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…The continuous development of bionanotechnology and nanomedicine, together with the intensification of research on EVs, has greatly contributed to the consideration of their potential as disease biomarkers, vaccine components, or the drug delivery vehicles, with a wide range of applications in the prevention, diagnosis, prognosis, and treatment of diverse medical conditions ( Ullah et al, 2023 ; Liu and Hu, 2023 ; Liu et al, 2024 ). EVs are currently considered as promising biomarkers for different disorders in the human organism, including infectious diseases, as the specific molecules they carry are not only protected from environmental destructive factors, but also transported long distances from the initial site of infection or tissue dysfunction, reaching body fluids such as blood, urine and saliva, where they can be collected from patients using a relatively non-invasive methods ( Raeven et al, 2018 ; Cifferi et al, 2021 ).…”
Section: Potential Applications Of Hevs and Fevs In Bionanotechnology...mentioning
confidence: 99%